Disturbance is the key to plant invasions in cold environments - Lembrechts, Jonas J.; Pauchard, Anibal; Lenoir, Jonathan; Nunez, Martin A.; Geron, Charly; Ven, Arne; Bravo-Monasterio, Pablo; Teneb, Ernesto; Nijs, Ivan; Milbau, Ann (My University, 2016)
Until now, nonnative plant species were rarely found at high elevations and latitudes. However, partly because of climate warming, biological invasions are now on the rise in these extremely cold environments. These plant invasions make it timely to undertake a thorough experimental assessment of what has previously been holding them back. This knowledge is key to developing efficientmanagement of the increasing risks of cold-climate invasions. Here, we integrate human interventions (i.e., disturbance, nutrient addition, and propagule input) and climatic factors (i.e., temperature) into one seed-addition experiment across two continents: the subantarctic Andes and subarctic Scandinavian mountains (Scandes), to disentangle their roles in limiting or favoring plant invasions. Disturbance was found as the main determinant of plant invader success (i.e., establishment, growth, and flowering) along the entire cold-climate gradient, explaining 40-60% of the total variance in our models, with no indication of any facilitative effect from the native vegetation. Higher nutrient levels additionally stimulated biomass production and flowering. Establishment and flowering displayed a hump-shaped response with increasing elevation, suggesting that competition is the main limit on invader success at low elevations, as opposed to low-growing-season temperatures at high elevations. Our experiment showed, however, that nonnative plants can establish, grow, and flower well above their current elevational limits in high-latitude mountains. We thus argue that cold-climate ecosystems are likely to see rapid increases in plant invasions in the near future as a result of a synergistic interaction between increasing human-mediated disturbances and climate warming.
Keywords: alien plant species; biological invasions; climate change; disturbance; mountains